Students’ perception towards android as an instructional media - Yari Dwikurnaningsih; Bambang Suteng Sulasmono (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
This study aimed at describing the perception of vocational high school students towards Android-based mobile learning including the display, accessibility, and benefit of instructional media that had evidently improved their learning outcomes. The research sample was taken purposively, which was an experiment class consisting of 37 students. The data-gathering technique employed the questionnaire of media perception developed according to Lewis’s perception theory. The research result showed that the students had a positive perception towards mobile learning on its display, accessibility, and benefit.